Is Big Blue 'Open' for Business? - Pinder, Richard (2010)
The vertical control of research and development (R&D) is becoming obsolete due to the increasing availability of useful knowledge. Industries that have relied on exclusivity or lag in exploiting their own discoveries are being challenged through the proliferation of players and better communication, which opens new opportunities for creating value. Joint ventures, spin-offs, better integration of university and industrial research, are all providing new routes to creating new products and services. This new approach is termed open innovation.